2012
DOI: 10.1155/2012/974786
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Local Neighbourhood Environment on Walking Levels during the Walking for Wellbeing in the West Pedometer-Based Community Intervention

Abstract: We investigated the relationship between walking levels and the local neighbourhood physical environment during the Walking for Wellbeing in the West (WWW) randomised pedometer-based community intervention. Walking activity was recorded as step counts at baseline (n = 76), and at 3 months (n = 57), 6 months (n = 54), and 12 months (n = 45) post-intervention. Objective physical environment data were obtained from GIS datasets and street surveys conducted using the SWAT audit tool. Sixty-nine environment variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 51 publications
(73 reference statements)
0
24
1
Order By: Relevance
“…In one of the Belgian studies, 34 participants living in high compared with low walkable neighbourhoods accumulated 1222 more steps/day (95% CI 131 to 2313). Although the estimates of the other Belgian study 35 and the Japanese study 37 were not conclusive, these also suggested a positive association between walkability and steps. The settings of these studies differ importantly from the Canadian context, possibly accounting for the difference in findings.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In one of the Belgian studies, 34 participants living in high compared with low walkable neighbourhoods accumulated 1222 more steps/day (95% CI 131 to 2313). Although the estimates of the other Belgian study 35 and the Japanese study 37 were not conclusive, these also suggested a positive association between walkability and steps. The settings of these studies differ importantly from the Canadian context, possibly accounting for the difference in findings.…”
Section: Discussionmentioning
confidence: 76%
“…Two were conducted in Belgium, 34 35 one in the Czech Republic 36 and one in Japan. 37 In the Czech study, 38 participants living in high compared with low walkable neighbourhoods accumulated 2088 more steps/day (95% CI 440 to 3736). In one of the Belgian studies, 34 participants living in high compared with low walkable neighbourhoods accumulated 1222 more steps/day (95% CI 131 to 2313).…”
Section: Discussionmentioning
confidence: 96%
“…The point estimates of all six studies suggested that higher walkability was associated with a greater number of daily steps. Based on the confidence intervals, these associations were conclusive for only three of these studies [ 30 , 32 , 33 ]. In addition to examining the role of walkability with daily steps, three of the six studies assessed the role of walkability on utilitarian walking [ 30 , 31 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the six studies were conducted in Europe (Belgium [ 30 , 31 ], Czech Republic [ 32 ], and Scotland [ 33 ]) and two of the six studies were conducted in Asia (China [ 34 ] and Japan [ 35 ]) (Table 1 ). All of the studies were cross-sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, community-based physical activity programs usually focus on a defined group of participants (e.g. retired senior people), in order to promote the importance of physical activity for improving quality of life [ 15 21 ]. Assessing the effectiveness of these programs has been a popular undertaking among researchers.…”
Section: Introductionmentioning
confidence: 99%